2021
DOI: 10.1002/jcsm.12753
|View full text |Cite
|
Sign up to set email alerts
|

Matrisome, innervation and oxidative metabolism affected in older compared with younger males with similar physical activity

Abstract: Background Due to the interaction between skeletal muscle ageing and lifestyle factors, it is often challenging to attribute the decline in muscle mass and quality to either changes in lifestyle or to advancing age itself. Because many of the physiological factors affecting muscle mass and quality are modulated by physical activity and physical activity declines with age, the aim of this study is to better understand the effects of early ageing on muscle function by comparing a population of healthy older and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 113 publications
5
9
0
Order By: Relevance
“…However, the populations used in the meta-analysis were very heterogeneous (e.g., trained and sedentary participants were included, and both young and adult participants were used as control groups), and the exact comparisons that were done were poorly described. Furthermore, it could be argued that mRNA levels encoding OXPHOS subunits do not necessarily translate into oxidative function; however, this is unlikely in the light of previously reported significant correlations between OXPHOS subunit levels and in vivo mitochondrial capacity in old and young male participants [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the populations used in the meta-analysis were very heterogeneous (e.g., trained and sedentary participants were included, and both young and adult participants were used as control groups), and the exact comparisons that were done were poorly described. Furthermore, it could be argued that mRNA levels encoding OXPHOS subunits do not necessarily translate into oxidative function; however, this is unlikely in the light of previously reported significant correlations between OXPHOS subunit levels and in vivo mitochondrial capacity in old and young male participants [22].…”
Section: Discussionmentioning
confidence: 97%
“…Well-studied drivers of age-related loss of muscle mass and strength include a decreased mitochondrial content or function [22,23]. One electron microscopy study measured mitochondrial content and found that intermyofibrillar mitochondrial size was primarily decreased in old females and not in old males [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies attempted to identify molecular changes associated with "healthy" aging in human skeletal muscle, considering primary aging with minimal contribution of physical impairment and chronic diseases. For this, different muscle molecular parameters were compared between physically active and sedentary elderly people (Hinkley et al, 2023;Lanza et al, 2008) or between young (sedentary) and older people with a comparable level of physical activity/performance (physically active) (Lagerwaard et al, 2021;Lanza et al, 2008;Murgia et al, 2017;Ubaida-Mohien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Lagerwaard et al . 2021; Monti et al . 2021) have availed ourselves of this to indirectly investigate myofibre innervation status in human muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a strong upregulation of the acetylcholine receptors (AChR), normally confined to the NMJ, is evident along the length of the myofibre upon denervation (Merlie et al 1984). We (Karlsen et al 2019(Karlsen et al , 2020Soendenbroe et al 2019Soendenbroe et al , 2020 and others (Gigliotti et al 2015;Baehr et al 2016;Kelly et al 2018;Sonjak et al 2019;Daou et al 2020;Skoglund et al 2020;Lagerwaard et al 2021;Monti et al 2021) have availed ourselves of this to indirectly investigate myofibre innervation status in human muscle tissue.…”
Section: Introductionmentioning
confidence: 99%